Analytical Study for the Ability of Some Polymers to Gain Transitional Elements Ionsions in Different Temperature, PH Acidity Functional and Time Situations - Abdulrahman R. Mahmood (Journal of Global Pharma Technology, 2016)
The compound [K1] was synthesized from the reaction of dichloromethane with linear alkyl benzene (Lab9) using ethanol as a solvent, and from(chloro methyl)-4-nonylbenzene) [K1] it was possible to synthesize the compound Z(4-(nonan-3-yl)phenyl) methane amine) [K2] containing the amine group by synthesized from [K2] reaction with appropriate phenolic aldehydes and using Ethanol as a solvent in the preparation of vinyl chloride4-(((4-nonylbenzyl)imino)methyl)phenol-4-(((4-nonylbenzyl)imino methyl)benzene-1,3diol) [K3-K4] bases has been used. Preparation of a number of Phenolic polymers4-(2-hydroxy-3.5-dimethylbenzyl)-2-methyl-6-(((4-4-(2hyroxy-3, 5-dimethylbenzyl)-2-methyl-6(((4 nonylbenzyl) imino) methyl) benzene-phenolnonylbenzyl) imino) methylbenzene-1,3iol [K5-K6] has been used from the reaction of K3-K4 with phenol formaldehyde. The analytical capacity of chelating resins prepared using the meal supply method for some of the transition element ions (Co+2, Fe+3, Cu+2) can be studied. The loading range for resins can be determined and the effect of the treatment time and pH is determined, with the temperature and concentration of the ions under study and the amount of resin this study shows that the loading capacity of resins increases as the processing time and pH increases. The compounds synthesized above in this study were identified by infrared spectroscopy (IR), H-NMR (1), and mass thermodynamic analysis (TG, DTG).Keyword: Phenolic Schiff base derivative, Polymer, Chloromethane, Aldehydes Phenolic.